Hubungan Antara Paparan Debu Dengan Kejadian Gangguan Saluran Pernafasaan Pada Masyarakat Kelurahan Kairagi Satu Lingkungan 3 Kota Manado. - Thaib, Yulina Purnamasari; Lampus, Bernadus.; Akili, Rahayu (JURNAL ADMINISTRASI PUBLIK, 2015)
Data case of respiratory tract disorders ISPA in the Province SulawesiUtara in 2014 showed that Kotamobagu city topped with total 15367 cases, followedsuccessively by Sangihe with total 9984 cases, followed successively by Manado City withtotal 4500 cases, followed successively by district Bolaang Mongondow Utara with total3153 cases, followed successively by district Minahasa Tenggara with total 1532 cases,followed successively by district Minahasa Utara with total 376 cases. Data cases ofrespiratory tract disorder ISPA in the in 2014 from Sanitary Depertement Of Manado Cityon frebruary total 153 cases, march total 1189 case, april total 679 cases, may total 1349cases, june total 685 cases, july total 79 cases, September total 216 cases, October total199 cases, novenber total 99 cases, December total 442 cases. According to research ofresults Dinda Anggun In Palembang 2013 that exposure to dust associated with eventsISPA a total of 34 people (48,6%) of the total population 70 people. According to researchof Yusnabeti etc in 2009, furniture industry workers in rural wes kern Cilebut that exposureto dust associated with events ISPA, who experiended ISPA 43 People from population 98people. According to research of khairiah etc in 2012, Sumatera utara that the dustconcentration associated with respiratory disorders 19 people, from total population 56people.Method : This research uses the type of survey research with cross sectional analyticstudy cross sectional design.Result : In test use Uji Chi-Square then get correlation value of 0,006 p < 0,05, meaningthat there is a relationship between exposure to dust with the incidence of respiratorydisorders in the community village Kairagi 1 enviroment 3 Manado city.Conclusion : The measurement results have two categories of medium and light. Mediumcategory of 38,6%. Light category of 61,4%. 45 respondents (64,3%) Who experiencerespiratory tract disorders (ISPA) in the Kairagi Village Environments 3 Manado city. 25respondents (35,7%) did not experience respiratory disorders (ISPA) in the Kairagi VillageI enviroments 3 Manado City. There is a relationship between exposure to dust with eventsrespiratory in the community in the Kairagi Village I enviroments 3 Manado City.Keywords : exposure to dust, the events of respiratory disorders